Automating Linux and Unix System Administration - Campi, Nathan; Bauer, Kirk (Apress : Imprint: Apress, 2009)
Whether you need a network of ten Linux PCs and a server or a data center with a few thousand UNIX nodes, you need to know how to automate much of the installation, configuration, and standard system administration. Build your network once using cfengine, and the network build will work, without user intervention, on any hardware you prefer. Automating Linux and Unix System Administration, Second Edition is unique in its focus on how to make the system administrator's job easier and more efficient: instead of just managing the system administrator's time, the book explains the technology to automate repetitive tasks and the methodology to automate successfully. Both new and seasoned professionals will profit from industry-leading insights into the automation process. System administrators will attain a thorough grasp of cfengine, kickstart, and shell scripting for automation. After reading all chapters and following all exercises in this book, the reader will be able to set up anything from a Linux data center to a small office network.